Revealing higher than expected diversity of Harpacticoida (Crustacea:Copepoda) in the North Sea using MALDI-TOF MS and molecular barcoding - Rossel, S. (Sci Rep, 2019)
The North Sea is one of the most extensively studied marine regions of the world. Hence, large amounts of molecular data for species identification are available in public repositories, and expectations to find numerous new species in this well-known region are rather low. However, molecular reference data for harpacticoid copepods from this area in particular but also for this group in general is scarce. By assessing COI barcodes and MALDI-TOF mass spectra for this group of small crustaceans, it was discovered that there is a huge unknown diversity in this area. In total, COI sequences for 548 specimens from 115 species of harpacticoid copepods are presented. Over 19% of these were new to science and ten MOTUs were found to be part of cryptic species complexes. MALDI-TOF mass spectra were assessed for 622 specimens from 75 species. Because results were in concordance with species delimitation by COI barcoding and also enabled recognition of possible cryptic species, the discriminative power of this technique for biodiversity assessments is highlighted. Findings imply, species diversity in this group may be largely underestimated and total species number can be expected to be much higher than previously assumed.